2021
DOI: 10.1016/j.psj.2021.101465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary serine supplementation on performance, egg quality, serum indices, and ileal mucosal immunity in laying hens fed a low crude protein diet

Abstract: This study was designed to evaluate the effect of dietary Ser on performance, egg quality, serum indices, and ileal mucosal immunity in laying hens fed low crude protein ( LCP ), essential amino acids ( EAA ) balanced diets. A total of 480 Hy-Line Brown layers at 24 wk of age were randomly assigned into 5 dietary treatments with 8 replicates of 12 birds each. Treatments included a control diet (16.49% CP), and 4 LCP, EAA balanced diets (14.05% CP) supplemented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The conventional layer diet contained sufficient essential amino acids and nonessential amino acids; however, it is possible that a low‐protein diet does not supply enough nitrogen for the synthesis of nonessential amino acids (Macelline et al, 2021). Additionally, Zhou et al (2021) reported that LPS supplemented with serine recovered the egg‐laying rate depending on the serine concentration. In the present study, the reduction of dietary CP of the low‐protein diet was relatively small (two percentage points), possibly resulting in sufficient dietary nitrogen for the synthesis of nonessential amino acids, and we designed the composition of the experimental diets based on the Japanese Feeding Standard for Poultry and ensured that they contained adequate amounts of essential amino acids and Gly + Ser (NARO, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The conventional layer diet contained sufficient essential amino acids and nonessential amino acids; however, it is possible that a low‐protein diet does not supply enough nitrogen for the synthesis of nonessential amino acids (Macelline et al, 2021). Additionally, Zhou et al (2021) reported that LPS supplemented with serine recovered the egg‐laying rate depending on the serine concentration. In the present study, the reduction of dietary CP of the low‐protein diet was relatively small (two percentage points), possibly resulting in sufficient dietary nitrogen for the synthesis of nonessential amino acids, and we designed the composition of the experimental diets based on the Japanese Feeding Standard for Poultry and ensured that they contained adequate amounts of essential amino acids and Gly + Ser (NARO, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A study found that as a coenzyme of mitochondria, LA can alleviate the loss of mitochondrial function due to aging and reduce the oxidative stress and inflammatory response of the ovary and oviduct ( 43 ), thus improving the reproductive pathway. Zhou et al ( 44 ) found that the addition of antioxidants improved performance probably through enhancing the immunity and attenuating inflammation of laying hens. Here in this study, it was found that OFO induced an increase in serum inflammatory factors, and the dietary addition of LAM significantly increased immunoglobulin (IgA, IgG, and IgM) levels and reduced the inflammatory factors (TNF-α, IL-1β, IL-6, and IFN-γ).…”
Section: Discussionmentioning
confidence: 99%
“…Upon breakage of each egg, the albumen and the yolk were separated with the aid of an egg separator, and the weight of each was recorded. To measure the thick and thin albumen fractions, the weighed albumen was placed in a 60-mesh sieve at a time bound of 30 s, the thick portion of the albumen was glued to the sieve while the thin portion passed through the sieve as filtrate, and the corresponding weight of each fraction was recorded ( Zhou et al, 2021 ). The eggshells were cleaned to remove any albumen fragments and then naturally dried for 48 h, and the weight was obtained.…”
Section: Methodsmentioning
confidence: 99%